Develop the controller for dual-mode thermosiphon beam - Chew, Kok Joon (Nanyang Technological University, 2020)
Air-conditioning is one of the greatest inventions in history. It brings comfort to the occupants by reducing the room temperature and relative humidity. In commercial buildings, offices and civil-service buildings, HVAC system increases the occupants’ working efficiency and public efficiency as occupants are more able to focus in their comfort zone. There are mainly 4 types of HVAC systems such as single-split system, multi-split system, VAV system and VRF system. The most common system is single-split system which mostly used in small offices, shops and houses while VAV system is used for a bigger cooling foot print such as healthcare centre, commercial malls and hotel. These HVAC systems require high power and energy supplies to provide an ideal indoor environment to the occupants. Not only that, VAV system requires long air ducting, chilled water pipes and air handling unit to deliver cool air to the occupied spaces. As the society started to take note of the sustainability issues and promote environmentally friendly systems, thermosiphon beam system has become new trend of HVAC. Besides that, thermosiphon beam system required low energy consumption and installation costs. Thermosiphon beam systems can be operated in 2 modes which are passive and active modes. However, an efficient controlling system is needed to control the operation of thermosiphon beams in both modes and provide a good indoor environmental quality to the occupants. The testing and development of the thermosiphon beam controller will be conducted in Energy Research Institute Lab in Nanyang Technological University.